Safety and effectiveness of additional triamcinolone acetonide with endoscopic radial incision and cutting for benign stenosis of the lower gastrointestinal tract: A pilot study - Rintaro Moroi; Kotaro Nochioka; Satoshi Miyata; Hideya Iwaki; Hirofumi Chiba; Hiroshi Nagai; Yusuke Shimoyama; Takeo Naito; Hisashi Shiga; Masaki Tosa; Yoichi Kakuta; Shoichi Kayaba; et al. (DEN Open)
Abstract Objectives Radial incision and cutting (RIC) is being investigated as an alternative endoscopic dilation method for lower intestinal tract stenosis, providing a high technical success rate and improving subjective symptoms. However, several patients develop re‐stenosis following RIC. In this pilot study, we aimed to evaluate the safety and efficacy of triamcinolone acetonide (TA) addition after RIC. Methods RIC with TA was performed in 20 patients with lower gastrointestinal tract stenosis. We evaluated the rate of adverse events 2 months after RIC with TA. We investigated the short‐ and long‐term prognoses, as well as the improvement in subjective symptoms, using a visual analog scale. Results The delayed bleeding rate after RIC was 23.8%. Endoscopic hemostasis was achieved in all patients with delayed bleeding. No perforations were observed. The cumulative re‐stenosis‐free, re‐intervention‐free, and surgery‐free rates 1 year after RIC were 52.9%, 63.7%, and 85.2%, respectively. Subjective symptoms, including abdominal pain, abdominal bloating, nausea, and dyschezia, significantly improved after RIC with TA. Conclusion Although additional TA administration after RIC could be safe, additional TA may not be effective on luminal patency after dilation. Further investigation is warranted.